Correction to: Genome-wide association study for stayability at different calvings in Nellore beef cattle (BMC Genomics, (2024), 25, 1, (93), 10.1186/s12864-024-10020-y) - Silva, Diogo Osmar [UNESP]; Fernandes Júnior, Gerardo Alves [UNESP]; Fonseca, Larissa Fernanda Simielli [UNESP]; Mota, Lúcio Flávio Macedo [UNESP]; Bresolin, Tiago [UNESP]; Carvalheiro, Roberto [UNESP]; de Albuquerque, Lucia Galvão [UNESP] (Springer Nature, 2024)
Following publication of the original article it was reported that the names of Gerardo Alves Fernandes Júnior and Lucia Galvão de Albuquerque were incorrectly published as ‘Gerardo Alves Fernandes’ and ‘Lucia Galvão Albuquerque’ respectively. The original article has been updated.